Tax-advantaged investments - Windish, David F. (Prentice-Hall, 1983)
This book provides the basics to build a strong working knowledge of investment, taking into account the special conditions of today's market - inflation, tax legislation, interest rates, ...It covers specific areas of potential tax-advantaged investment in real estate, oil, gas, equipment leasing, energy, agriculture, livestock, timber, entertainment, and other industries.